From Trust to Betrayal: Child Grooming in Indonesia's Legal Framework - Faisal, Fitriah (Department of Law, Universitas Islam Negeri Alauddin Makassar, 2024)
This study explores the gaps in Indonesia's legal system regarding child grooming. Through a normative legal research methodology, this study examines both national and international legal approaches to child grooming, highlighting how Indonesia’s current legal provisions inadequately capture the complex and manipulative nature of the crime. The paper also underscores the influence of cultural norms and religious beliefs that obscure the recognition of grooming as a serious form of child exploitation. By comparing Indonesia's laws with those of countries like the United Kingdom, Australia, and the United States. This study emphasizes the need for legal reform in Indonesia to explicitly criminalize child grooming and enhance child protection efforts. The findings reveal a significant need for clearer definitions, preventive measures, and legal accountability to safeguard children from exploitation under the guise of familial consent or cultural practices.